2016
DOI: 10.1590/0100-3984.2013.0007
|View full text |Cite
|
Sign up to set email alerts
|

Knee bone tumors: findings on conventional radiology

Abstract: The knee is a common site for bone tumors, whether clinically painful or not. Conventional radiology has been established as the first line of investigation in patients with knee pain and can reveal lesions that often generate questions not only for the generalist physician but also for the radiologist or general orthopedist. History, image examination, and histopathological analysis compose the essential tripod of the diagnosis of bone tumors, and conventional radiology is an essential diagnostic tool in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 6 publications
0
4
0
9
Order By: Relevance
“…This may be because some imaging features of intermediate bone tumors are similar to those of benign or malignant bone tumors. For example, giant cell tumor of bone appears as an eccentric lytic lesion without marginal sclerosis and may have cortical destruction on radiography [ 22 , 23 ], and eosinophilic granuloma of the bone appears as a moth-eaten lytic-bone lesion without marginal sclerosis, but with a continuous periosteal reaction [ 24 ]. Retrospective analysis of misclassified cases in this study revealed that 92.3% of misclassifications involved benign vs. intermediate bone tumors or malignant vs. intermediate bone tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because some imaging features of intermediate bone tumors are similar to those of benign or malignant bone tumors. For example, giant cell tumor of bone appears as an eccentric lytic lesion without marginal sclerosis and may have cortical destruction on radiography [ 22 , 23 ], and eosinophilic granuloma of the bone appears as a moth-eaten lytic-bone lesion without marginal sclerosis, but with a continuous periosteal reaction [ 24 ]. Retrospective analysis of misclassified cases in this study revealed that 92.3% of misclassifications involved benign vs. intermediate bone tumors or malignant vs. intermediate bone tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Las características radiográficas que ayudan a realizar un diagnóstico de tumor óseo, o al menos a disminuir las posibilidades diagnósticas, incluyen los patrones de destrucción ósea (geográfica, apolillada, permeativo), los márgenes lesionales (bordes esclerosos, activos o agresivos), las características internas de la lesión (lesiones blásticas o líticas), el tipo de respuesta ósea (medular o perióstica), la localización, el sitio (metáfisis, diáfisis o epífisis), la posición de la lesión en el cuerpo y en el hueso afectado (central, excéntrica o perióstica), la afectación de partes blandas y las lesiones únicas o múltiples [1][2][3] .…”
Section: Introductionunclassified
“…Desafortunadamente, aun cuando las características radiológicas de las lesiones tumorales óseas han sido descritas bajo ciertos criterios de diagnóstico 2,3,10 , existen carencias en las aproximaciones cuantitativas de la presentación de las características radiológicas y su asociación con el diagnóstico final. Se han descrito las características de los quistes óseos aneurismáticos y reportaron las frecuencias de presentación de cada característica encontrada 11 , y en la literatura existe también el análisis de las características radiográficas para condrosarcomas 12 , fibroma no osificante 13 , granuloma eosinófilo 14 y quistes óseos unicamerales 15 .…”
Section: Introductionunclassified
“…In most cases, the method used for the initial identification, characterization, and classification of "don't touch" lesions is conventional X-ray. The integrated analysis between the imaging findings and the clinical and laboratory data is essential ( 2 ) .…”
mentioning
confidence: 99%